Energy supply affects leucine utilization by growing steers - G.F. Schroeder; E.S. Moore; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2007)
In growing pigs, when protein supply is adequate, protein deposition increases with an increase in energy intake. However, when amino acid supply is limited, protein deposition does not respond to increases in energy intake. These relationships between energy, protein supply and protein deposition, which are observed in monogastric animals, have been described as protein- and energydependent phases of growth. These relationships indicate that energy supply does not affect the efficiency of amino acid utilization, allowing the assumption of a constant efficiency across a broad range of energy intake. Although this type of relationship is assumed for cattle by most of the nutrient requirements systems, our previous experiments indicate that energy supply increases the efficiency of methionine utilization, challenging the assumption of a single efficiency of amino acid use. It is unknown, however, if the positive effects of energy supply on methionine utilization are of similar magnitude for other amino acids. The objective of our study was to determine the effect of energy supply on leucine utilization in growing steers.
Keywords: Cattlemen' s Day; 2007; Kansas Agricultural Experiment Station contribution; no. 07-179-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 978; Beef; Cattle; leucine; Steers